THE ROLE OF THE FARMER WOMEN'S GROUP (KWT) IN INCREASING THE INCOME OF FARMER FAMILIES IN SRAGEN REGENCY - Lestari, Retna Dewi; Sari, Intan Lukita; Sari, Vinanda Puspita (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Data analysis to determine the effect of the role of KWT on the family income of farm women is to perform a simple linear regression analysis. Based on the results of the regression test, it is known that the calculated t value on the effect of the role of KWT on the income of farm women's families results is a significant influence between the role of KWT and the income of farmer women's families. The average income of farm women in managing farming activities is Rp 729,200, the income is used to help meet the needs of the family. Based on the results of interviews with farmer women, the income of farmer women from the KWT business unit and their own business is used for school fees, buying daily food needs and social community needs such as social gatherings, garbage dues, and others. The role of farmer women's groups in increasing the income of farm women's families is shown from the many types of businesses run by farm women. The average group of peasant women in Sragen Regency has a business unit as a source of business income. These business units include herbal medicine agribusiness units ranging from cultivation to marketing of herbal products, hydroponic agribusiness, and other business units.